Pilot Study for the In Situ Conservation of Wild Wheat Progenitors, Triticum monococcum subsp. aegilopoides and Aegilops speltoides var. ligustica in Mesti Area, Greece - Tsivelikas, Athanasios (International Center for Agricultural Research in the Dry Areas, 2023)
Pilot Study for the In Situ Conservation of Wild Wheat Progenitors, Triticum monococcum subsp. aegilopoides and Aegilops speltoides var. ligustica in Mesti Area, Greece.